(untitled) (Orinoquia, 2021)
The Ionization Potential (IP) of chemical species is of paramount importance for the Matrix Assisted Laser Desorption/Ionization (MALDI) analytical technique. Specifically, IPs are used in MALDI MS Electron Transfer (ET) as a parameter to select the matrix for a given family of chemical species. We used a quantum chemical methodology to computationally determine IPs for a set of photosensible phytoplanktonic pigments. These calculations could be used as a guide for MALDI matrix selection. IPs were determined using Koopman’s Theorem, via Geometry Optimization and Single Point Energy within the Restricted Closed-Shell Hartree-Fock (RHF) technique. Structures of a twenty-four set of pigments were geometrically optimized, and their IPs determined. Calculated IP’s are in close agreement to reported experimental IPs within an average 3.7% absolute error. Structural features of the chemical species studied have a closed relationship with their chemical properties and IP’s. Our results suggest that ET-MALDI matrices such as DCTB (IP = 8.5 eV) and CNPV-OCH3 (IP = 8.3 eV) could be more suitable to analyze these types of chemical species.